Total Quality Management Strategy to Improve Organizational Culture in Multicultural and Religious-Based Educational Institutions - Daoreji Saengchuk; Sorombun Phammesone; Prasminata Traorésa; Ahmed Zeaman Solomon; Mohammed Baiq Mose (International Journal of Education Management and Religion, 2024)
This study aims to analyze the implementation of Total Quality Management (TQM) in improving organizational culture in religious and multicultural-based educational institutions. The primary focus of this research is to identify the key elements in the application of TQM, including effective leadership, staff involvement, process orientation, resource management, continuous improvement, and data-driven approaches. The research method used is a literature study by examining various sources related to the application of TQM in education. The findings indicate that effective TQM implementation can enhance educational quality by strengthening organizational culture that is inclusive, high-quality, and sustainable. Effective leadership plays a crucial role in ensuring the integration of multicultural and religious values into institutional policies, while staff involvement in decision-making and resource management increases commitment to educational goals. Additionally, continuous improvement through the PDCA cycle has been proven to help educational institutions adjust policies and procedures to support diversity. The data-driven approach and performance measurement also show significant success in achieving the desired educational goals. This study concludes that the application of TQM principles in religious and multicultural-based educational institutions can create a more inclusive learning environment and improve educational quality sustainably.